2013
DOI: 10.1111/aji.12132
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial CD16+and CD16NK Cell Count in Fertility and Unexplained Infertility

Abstract: Increased CD16(+ ) NK cells were associated with IL-6 and VEGF deficiency in a high proportion of UI-IF patients. Testing for these immunomarkers could be a potential tool in infertility diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 29 publications
(43 reference statements)
1
28
0
Order By: Relevance
“…In addition, Fukui et al 15 observed an increase of the percentage of CD16 + CD56 dim cells and decrease in the percentage of CD16 − CD56 bright cells in women with infertility who miscarried after IVF cycles compared with women who delivered. Most recently, Junovich et al 18 reported an increased number of CD16 + endometrial NK cells in patients with unexplained infertility that correlated with a decrease in endometrial IL-6 and VEGF levels. Therefore, it can be hypothesized that an increase in “activated” CD16 + uNK cells may create an unfavorable environment for implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Fukui et al 15 observed an increase of the percentage of CD16 + CD56 dim cells and decrease in the percentage of CD16 − CD56 bright cells in women with infertility who miscarried after IVF cycles compared with women who delivered. Most recently, Junovich et al 18 reported an increased number of CD16 + endometrial NK cells in patients with unexplained infertility that correlated with a decrease in endometrial IL-6 and VEGF levels. Therefore, it can be hypothesized that an increase in “activated” CD16 + uNK cells may create an unfavorable environment for implantation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, while some previous case-control studies report a higher concentration of uNK cells in women with uRPL compared to fertile women 9,10,11,12,13 , other studies did not find this association 5,14 . Similarly, evidence exists for both an association and lack of association between uNK cell number/function and infertility 15,16,17,18 . Only few studies have examined changes of uNK cell numbers in endometriosis, demonstrating a lower percentage of CD56 + NK cells and a defect in NK activity in the eutopic endometrium of women with endometriosis 19, 20, 21, 22 .…”
Section: Introductionmentioning
confidence: 99%
“…Special focus has been on IL6, a key mediator of immune and acute phase responses, as several studies indicate that dysregulation of IL-6 may disturb implantation and be harmful to pregnancy [32, 33]. IL-6 is a key cytokine that blocks the development of regulatory T (Treg) cells and induces the differentiation of Th17 cells.…”
Section: Methodsmentioning
confidence: 99%
“…However, they considered that the value of measuring NK cell activity or number as a prognostic indicator of pregnancy success was still undetermined. On the other hand, various reports have documented the usefulness of measuring pre-pregnancy peripheral blood or endometrial NK cells as an indicator of reproductive success [6][7][8][9][10][11][12][13][14][15][16][17][18]. NK cell cytotoxicity at the time of embryo transfer is significantly higher in women who miscarry [9], and the count of pre-pregnancy peripheral CD56 ?…”
Section: Introductionmentioning
confidence: 99%
“…/CD56 dim NK cells is also significantly higher in women who miscarry [9] or those with RPL [18]. In women with reproductive failure, pre-pregnancy cytokine production by NK cells shows a shift from type 2 to type 1 [11], and expression of NK cell activating and inhibitory receptors also alters [10,[12][13][14]17].…”
Section: Introductionmentioning
confidence: 99%